Economic stress from climate change on agriculture: a SAM-based assessment - Watchara Pechdin; Pongsun Bunditsakulchai (Environmental Research Communications)
Climate change poses a significant threat to global agricultural sectors and their supply chains, with far-reaching implications for economic stability and growth, particularly in developing countries heavily reliant on agriculture. In this study, we employ a Social Accounting Matrix (SAM) framework to analyze the linkages between the agricultural sector and the broader economy and to assess the potential economic losses from climate change to inform stakeholders of its wider impacts. By analyzing three scenarios of agricultural production declines (0.1%, 0.2%, and 0.3%), we can quantify the economic loss thresholds, which include production losses, household losses, and circular effects from injected income across both agricultural and non-agricultural sectors. Our calculations reveal that even minor reductions in agricultural output lead to substantial economic losses, with a 0.1% decline resulting in an 11.04 billion THB (0.32 billion USD) loss, escalating to 33.11 billion THB (1.01 billion USD) for a 0.3% decline. At the sectoral level, production losses were most concentrated in input-supplying industries such as chemicals, machinery, and energy. From a household perspective, farmers in the rubber and sugarcane sectors were among the most affected. Additionally, sectors like wholesale and retail trade experienced losses due to disruptions in economic circulation. These findings highlight the importance of strengthening the resilience of agriculture-related industries and reforming the agricultural sector to align with their consumption and production patterns. Such measures are crucial for ensuring sustainable agricultural development in response to climate change.